2016
DOI: 10.1016/j.oceaneng.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A scaling procedure for modern propeller designs

Abstract: The extrapolation procedures currently used to scale propeller characteristics tested at model scale to their full scale performances are either based on a statistical [1], the Lerbs-Meyne [2] or the recently developed strip method [3]. With the emergence of so-called unconventional propellers and different design strategies associated with them, it has been questioned whether the assumptions used in these scaling methods are still universally valid. E.g. with tip and root unloading employed, the circulation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Helma [4,5] showed that the mean hydrodynamic inflow angleβ i into an equivalent profile can be calculated from the open-water test as follows:…”
Section: β I -Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Helma [4,5] showed that the mean hydrodynamic inflow angleβ i into an equivalent profile can be calculated from the open-water test as follows:…”
Section: β I -Methodsmentioning
confidence: 99%
“…a Streckwall et al specified the Reynolds numbers of the transition point x t for the open-water condition as 4×10 5 (suction side) and 2×10 5 (pressure side), and for the behind condition as 3×10 5 (suction side) and 1×10 5 (pressure side) [9]. b In his presentation, Schulze has an obvious misprint when giving the value of 0.03 for the middle part [7].…”
Section: Friction Lines For Transition Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the performance of a full scale propeller is not commonly available, novel methodologies have been proposed to scale the open-water data from tests performed at different Re numbers to the full scale propeller [5,6]. The power and shaft revolutions were predicted on a series of different scaling methods.…”
Section: Introductionmentioning
confidence: 99%